2021
DOI: 10.1186/s12933-021-01322-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of empagliflozin on cardiac physiology and fibrosis early after myocardial infarction in non-diabetic rats

Abstract: Background Myocardial fibrosis is a multistep process, which results in collagen deposition in the injured muscle. Empagliflozin, a sodium-glucose cotransporter 2 inhibitor (SGLT2i), decreases cardiovascular events risk. Little is known on the effects of empagliflozin in non-diabetic patients early post myocardial infarction. Methods Fourteen non-diabetic rats underwent myocardial infarction induction, and treated or not (control)immediately after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…Kang et al showed in an in vitro set-up, that collagen deposition reduction may involve the inhibition of the TGF-β1/smad3 pathway [9]. Lately, we have shown in an in vivo set-up that empagli ozin attenuates TGF-β1/smad3 expression, and concomitantly, affected collagen deposition in non-diabetic rats post MI [10], thus, establishing further the involvement of this pathway in brosis.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…Kang et al showed in an in vitro set-up, that collagen deposition reduction may involve the inhibition of the TGF-β1/smad3 pathway [9]. Lately, we have shown in an in vivo set-up that empagli ozin attenuates TGF-β1/smad3 expression, and concomitantly, affected collagen deposition in non-diabetic rats post MI [10], thus, establishing further the involvement of this pathway in brosis.…”
Section: Introductionsupporting
confidence: 72%
“…Smad3 is an essential component in the signaling pathway of TGF-β, which rests downstream to the TGF-β receptors [32]. Lately, we showed that empagli ozin, a sodium/glucose transporter 2 inhibitor, also attenuate the TGF-β1/smad3 pathway and prevent post-MI brosis and preserves cardiac structure [10]. Here, we show that spironolactone, but not TUS, affects the downstream components of this pro-brotic pathway, smad3 [32].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It is well documented that the intracellular effectors of empagliflozin include extracellular signal-regulated kinase 1/2 [ 65 ], phosphoinositide 3-kinase/Akt [ 18 ], transforming growth factor β1 [ 66 ], nuclear factor κB [ 67 ], Janus kinase 2 [ 67 ], Sirtuin 1 [ 68 ], hypoxia inducible factor 1α [ 69 ], protein kinase G Iα [ 70 ], heme oxygenase 1 [ 71 ], peroxisome proliferator-activated receptor gamma coactivator 1α [ 72 ] and AMPKα1 [ 20 ]. Among them, AMPK has been identified as an indispensable inducer of mitophagy.…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2i can improve cardiac structural remodeling (Chowdhury et al, 2020;Madonna et al, 2020;Sun et al, 2020;Shentu et al, 2021). EMPA was reported to affect the oxidative stress and fibrosis by inhibiting the TGF-β/Smad signaling pathway Daud et al, 2021) and activate the Nrf2/ARE signaling pathway in cardiomyocytes in the T2MD mouse model . DAPA also inhibits fibroblast activation and myocardial fibrosis (Shih et al, 2021;Tian et al, 2021) by inhibiting the TGF-β/Smad signaling pathway (Tian et al, 2021) in T2MD rats.…”
Section: Sglt2i Can Ameliorate Myocardial Inflammation and Structural...mentioning
confidence: 99%